PENYUSUNAN DAN DISAIN SOAL ULANGAN BAHASA INGGRIS BERBASIS MODUL SOFTWARE MULTIMEDIA - I Nengah Astawa; Ni Nengah Dwi Handayani; I Ketut Wardana (SPHOTA: Jurnal Linguistik dan Sastra, 2018)
Abstrak The study of English assessment investigated the types and quality of test distributed to junior high school students and develop it into a software based test module. The study aimed to know how valid and reliable is the multiple-choice test as a competence measurement device. The method or the design of the study applied the research and development with 4D phases, namely define, design, develop, disseminate through 1) checking syllabus, observing learning process, and constructing test items as module draft (INPUT), 2) considering validity and reliability of the test from the expert including trying out the tests (PROCESS); and 3) designing the appropriate test items into software products (OUTPUT). The source of data was taken from the result of observation sheet, interview sheet, questionaire and the the result of tryout of model tests given to SMPN 2 and SMPN 3 Mengwi students. The result of the study after being analysed quantitatively showed that 63 test items was valid and 37 was invalid. The fifty-valid test was distributed to students of SMPN 3 Mengwi. Based on the result, the mean score was 72.53. 21 of 40 students passed the minimum passing grade achievement ank and 19 students still needed improving. The highest score was 95 and the lowest one was 26. The medium was 78 and the mode was 53. After measuring the reliability level, the standard deviation ranged 0.50 – 1.00. meaning that the test was appropriate to be applied as measuring device.The valid test was then reconstructed to be raw material of software module. Kata Kunci ; test, module, Software, validity, reliability